Role of glial-cell-derived neurotrophic factor in salivary gland stem cell response to irradiation. Issue 3 (September 2017) - Peng, Xiaohong; Varendi, Kärt; Maimets, Martti; Andressoo, Jaan-Olle; Coppes, Rob P.
Abstract: Background and purpose: Recently, stem cell therapy has been proposed to allow regeneration of radiation damaged salivary glands. It has been suggested that glial-cell-derived neurotrophic factor (GDNF) promotes survival of mice salivary gland stem cells (mSGSCs). The purpose of this study was to investigate the role of GDNF in the modulation of mSGSC response to irradiation and subsequent salivary gland regeneration. Methods: Salivary gland sphere derived cells of Gdnf hypermorphic (Gdnf wt/hyper ) and wild type mice (Gdnf wt/wt ) were irradiated (IR) with γ-rays at 0, 1, 2, 4 and 8 Gy. mSGSC survival and stemness were assessed by calculating surviving fraction measured as post-IR sphere forming potential and population doublings. Flow cytometry was used to determine the CD24 hi /CD29 hi stem cell (SC) population. QPCR and immunofluorescence was used to detect GDNF expression. Results: The IR survival responses of mSGSCs were similar albeit resulted in larger spheres and an increased cell number in the Gdnf wt/hyper compared to Gdnf wt/wt group. Indeed, mSGSC of Gdnf wt/hyper mice showed high sphere forming efficiency upon replating. Interestingly, GDNF expression co-localized with receptor tyrosine kinase (RET) and was upregulated after IR in vitro and in vivo, but normalized in vivo after mSGSC transplantation. Conclusion: GDNF does not protect mSGSCs against irradiation but seems to promote mSGSCs proliferation through the GDNF-RET signaling pathway. Post-transplantation stimulation of GDNF/RET pathway may enhance the regenerative potential of mSGSCs.